2020
DOI: 10.18203/issn.2454-5929.ijohns20201533
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of thyroid swellings

Abstract: <p class="abstract"><strong>Background:</strong> Diseases of the thyroid continue to be a common clinical problem having a prevalence rate of 4 to 7% in the general population.</p><p class="abstract"><strong>Methods:</strong> This retrospective study was conducted in the Department of ENT, Head and Neck Surgery, SMGS Hospital, Jammu from January 2018 to January 2020. A thorough history taking, meticulous clinical examination, routine hematological and biochemical inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
3
2
0
Order By: Relevance
“…The malignant diseases in the study were 3.9% which is comparable to the study by Jaiswal et al, 2020 [3] and Gupta et al, 2020 [14] having 5.23% and 5% malignant cases. However, Chavan et al, 2016 [9] reported lower prevalence of malignant cases while Sengupta et al, 2011 [5] revealed higher number of cases of 9.55%.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The malignant diseases in the study were 3.9% which is comparable to the study by Jaiswal et al, 2020 [3] and Gupta et al, 2020 [14] having 5.23% and 5% malignant cases. However, Chavan et al, 2016 [9] reported lower prevalence of malignant cases while Sengupta et al, 2011 [5] revealed higher number of cases of 9.55%.…”
Section: Discussionsupporting
confidence: 85%
“…The previous studies by Gupta et al, 2020 [14] , Likhar et al, 2013 [14] and Prasad et al, 2020 [10] also showed comparable results. The study done by Gupta et al, 2020 [14] done on 60 patients revealed that 66.67% patients were diagnosed with colloid goiter and 3.33% patients with thyroiditis as benign category.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Acharya et al (2019) also had similar distribution of benign and malignant thyroid lesions with 77 cases of 87 studied cases found to be benign in nature (88.5%). Rates of thyroid malignancies in various other studies were 6%, 11.8%, 20%, 20% and 22%, respectively (Dorairajan et al, 1996;Rout et al, 2011;Kapoor et al, 2018;Gupta et al, 2020;Sarangi et al, 2021).…”
Section: Thyroid Tumoursmentioning
confidence: 86%